Transactional Distance in MOOCs: A Critical Analysis of Dialogue, Structure, and Learner Autonomy - Rick Shearer; Andrea Gregg; K. P. Joo; Kimberly Graham (Adult Education Research Conference, 2014)
Drawing upon a content analysis of students’ postings on CourseTalk.org, this study presents preliminary findings of analyzing transactional distance in xMOOCs in order to elucidate the educational exchange facilitated or restricted with reference to the three variables of transactional distance theory.